The Evaluation of the Neuroprotective Effect of a Single High-Dose Vitamin D3 in Patients with Moderate Ischemic Stroke - Omid Hesami; Setare Iranshahi; Shima Zareh Shahamati; Mohammad Sistanizd; Elham Pourheidar; Rezvan Hassanpour (Stroke Research and Treatment)
Introduction. Vitamin D insufficiency is highly prevalent and is a negative predictor for survival in ischemic stroke patients. We evaluated the effect of a high dose of vitamin D3 on the Neuron-Specific Enolase (NSE) level, National Institute of Health Stroke Scale (NIHSS), and Barthel Index (BI) scoring system in moderate ischemic stroke patients. Methods. This prospective, double-blind, randomized clinical trial (RCT) study was conducted from April 2020 to March 2021. Patients with moderate ischemic stroke (NIHSS 5 to 15) who had vitamin D deficiency (serum 25-OH vitamin D ≤30 ng/mL) were recruited and randomized into intervention and control groups. Subjects in the intervention group received a single dose, intramuscular (IM) injection of 600000 international unit (IU) vitamin D3, in addition to the standard treatment. NSE level and NIHSS were evaluated at baseline and 48 hours after the intervention. The BI was monitored three months after discharge. Results. During the study period, 570 patients were assessed; finally, forty-one patients completed the study. Except for the age which was higher in the control group (p=0.04), there were no statistically significant differences in other baseline characteristics between the two groups. After 48 hours, the NIHSS score was significantly lower in the intervention group (median 8 vs. 6.5, p=0.008 in the control and intervention groups, respectively), but there was no significant difference in the NSE level (p=0.80). Three months after discharge, the BI was significantly higher in the intervention group (median 8 vs. 9, p=0.03 in the control and intervention groups, respectively). Conclusions. Administration of a single 600000 IU of vitamin D3 could have neuroprotective effects in patients with moderate ischemic stroke, according to its significantly positive effects on functional clinical outcomes (NIHSS and BI), but this effect on the biomarker related to neural damage (NSE) was not significant.